Development of immature stages of Chrysoperla externa fed on nymphs of Bemisia tabaci biotype B reared on three hosts - Silva, Cláudio Gonçalves; Souza, Brígida; Auad, Alexander Machado; Bonani, Jean Patrick; Torres, Lucas Castro; Carvalho, César Freire; Ecole, Carvalho Carlos (Pesquisa Agropecuaria Brasileira, 2004)
Insects of the Chrysopidae family have been found on eggs and nymphs of whitefly in several ecosystems. The aim of this work was to evaluate the duration and survival of the immature stages of Chrysoperla externa (Hagen, 1861), fed on nymphs of Bemisia tabaci (Gennadius, 1889) biotype B reared on leaves of cucumber (Cucumis sativus), kale (Brassica oleracea) or wild poinsettia (Euphorbia heterophylla). Leaf discs from the hosts containing nymphs of whitefly were placed in Petri dishes containing 1% agar and maintained at 25±1ºC, 70±10% RH and a 12-hour photophase. One recently hatched larvae of C. externa was placed in each dish, in ten replications. The duration and survival of each instar, larval, prepupal and pupal phases were determined, as well as the weight after 24 hours in each instar and phase of development was recorded. The species of host plant of the whitefly affected the duration of the first and third instar of C. externa larvae, with a reduction in the larval period when they were fed on preys from cucumber leaves. Prepupal phase was lengthened in wild poinsettia leaves. Weights were affected by the kind of the whitefly host, however, this effect do not affect the survival of the immature stages.